2007
DOI: 10.1039/b701436h
|View full text |Cite
|
Sign up to set email alerts
|

The environmental behaviour of polychlorinated phenols and its relevance to cork forest ecosystems: a review

Abstract: Pentachlorophenol (PCP) has been used as a herbicide, biocide and preservative worldwide since the 1930s and as a result, extensive and prolonged contamination exists. The environmental impact increases when its many degradation products are taken into consideration. A number of chloroanisols and their related chlorophenols have been found in cork slabs collected from Portuguese oak tree forests before stopper manufacturing, and contamination by PCP and polychlorinated anisole (PCA) has been detected in Canadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Many studies have shown that, for some compound classes, the degradation products of primary pollutants can be more significant in terms of toxicity (e.g. McLellan et al 2007) and, coupled with compound specific differences in environmental partitioning, can adjust the chemical exposure profile (e.g. Edgar et al 2003Edgar et al , 2006, compromising accepted chemical behavioural models.…”
Section: Environmental Behaviour Of Pollutantsmentioning
confidence: 99%
“…Many studies have shown that, for some compound classes, the degradation products of primary pollutants can be more significant in terms of toxicity (e.g. McLellan et al 2007) and, coupled with compound specific differences in environmental partitioning, can adjust the chemical exposure profile (e.g. Edgar et al 2003Edgar et al , 2006, compromising accepted chemical behavioural models.…”
Section: Environmental Behaviour Of Pollutantsmentioning
confidence: 99%
“…They also have substantial applications in agriculture as herbicides, insecticides and fungicides. Due to their moderate bioaccumulation and high toxicity, they can cause serious health hazards, which depend on the degree of chlorination and the position of the chlorine atoms [1,2], and most of them are determined as priority contaminant by the US Environmental Protection Agency [3]. Therefore, developing reliable, sensitive and simple methods is of great interest for the determination of phenols in environmental, food, and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroanisoles, specially 2,4,6-trichloroanisole (2,4,6-TCA) and pentachloroanisole (PCA) are significant environmental pollutants frequently detected in many ecosystems such as different types of soils (Palm et al, 1991;D'Angelo and Reddy, 2000), river and marine sediments (Barakat et al, 2002), lake and river waters (Nystrom et al, 1992;Jiang et al, 2000), marine troposphere (Führer and Ballschmiter, 1998), and vegetable materials like the bark of the cork-oak in Mediterranean forests (McLellan et al, 2007). Chloroanisoles arise as a consequence of a detoxification reaction of highly toxic chlorophenolic pesticides, which consists in the Omethylation of their reactive hydroxyl group (Cserjesi and Johnson, 1972;Gee and Peel, 1974).…”
Section: Introductionmentioning
confidence: 99%